2021
DOI: 10.1007/s40615-021-01024-5
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating Asian American Cigarette and Alternative Tobacco Product Use: Results from the National Health Interview Survey (NHIS) 2006–2018

Abstract: Introduction Asian Americans suffer high rates of smoking and tobacco-related deaths, varying by ethnic group. Trends of cigarette and alternative tobacco product use among Asian Americans, specifically considering ethnic group, sex, and nativity, are infrequently reported. Methods Using National Health Interview Survey (NHIS) data from 2006–2018 and the 2016–2018 alternative tobacco supplement (e-cigarettes, cigars, smokeless tobacco, pipes), we explored cigarette and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…While tobacco use did not differ significantly by acculturation among the Asian subgroups in this study, trends towards higher tobacco use among highly acculturated other Asians, which includes Koreans, is consistent with what has been documented in the literature: a study of Koreans living in California found that acculturated Korean women were more likely to smoke compared to their bicultural or traditional counterparts [29] . Heterogeneity in tobacco use exists among Asian subgroups [30] , with US born Filipinos more likely to report daily smoking compared to foreign born Filipinos (12.6% vs. 7.5%). Furthermore, acculturation has been linked to an overall increase in smoking patterns among Asian American subgroups in California, possibly due to greater social acceptance towards smoking [31] .…”
Section: Discussionmentioning
confidence: 99%
“…While tobacco use did not differ significantly by acculturation among the Asian subgroups in this study, trends towards higher tobacco use among highly acculturated other Asians, which includes Koreans, is consistent with what has been documented in the literature: a study of Koreans living in California found that acculturated Korean women were more likely to smoke compared to their bicultural or traditional counterparts [29] . Heterogeneity in tobacco use exists among Asian subgroups [30] , with US born Filipinos more likely to report daily smoking compared to foreign born Filipinos (12.6% vs. 7.5%). Furthermore, acculturation has been linked to an overall increase in smoking patterns among Asian American subgroups in California, possibly due to greater social acceptance towards smoking [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Future studies might extend our model by examining preexisting alcohol consumption patterns and intrapersonal factors (e.g., internalized racism, racial trauma symptoms) that may moderate depressive symptomatology and drinking to cope motives vis-à-vis COVID-19 racism. Similarly, we encourage work that analyzes other empirically confirmed social-cognitive correlates of alcohol use severity—such as alcohol values and expectancies and peer influence ( Iwamoto et al, 2010 )—as well as substance use behavior of known public health import for Asian American subgroups, such as tobacco ( Lew & Tanjasiri, 2003 ; Rao et al, 2021 ). Finally, our framework should be expanded to test key cultural and intersectional variables ( Keum et al, 2022 ; Keum & Choi, 2021 )) germane to the link among COVID-19 racism and alcohol use outcomes, given that acculturative dynamics and gender appear to typify “high risk” drinkers among Asian American emerging adults ( Cook et al, 2015 ; Iwamoto et al, 2019 ).…”
Section: Discussionmentioning
confidence: 91%
“…For example, tobacco exposure among different Asian American groups varies by national origin. There are exceptionally high rates of smoking in Filipino Americans and betel nut use in South Asian Americans 44,45 . Furthermore, studies have shown physicians provide smoking cessation counseling at lower rates to people of color 46 .…”
Section: Discussionmentioning
confidence: 99%
“…There are exceptionally high rates of smoking in Filipino Americans and betel nut use in South Asian Americans. 44,45 Furthermore, studies have shown physicians provide smoking cessation counseling at lower rates to people of color. 46 Moreover, underrepresented groups such as Native Americans face social and economic disparities that contribute to higher and possibly increasing smoking prevalence.…”
Section: Oral Cavity Cancermentioning
confidence: 99%